The Effect of the Standard Classics Exercise to React Quickly in Children Aged 8-9 Years.: Life Sciences -Physical Education - Polevoy, Georgiy Georgievich; Sablin, Andrew Borisovich; Chernishev, Stanislav Vladimirovich (International Journal of Life Science and Pharma Research, 2023)
The problem of developing children's coordination abilities is relevant and can be solved by using Classical exercises in physical education lessons at school. The study aimed to determine the standard classic exercise's effect on reacting quickly in children aged 8-9. The children in the control group were engaged in the usual school physical education program, and the children from the experimental group additionally performed a traditional exercise classic. All children were engaged in physical education for 40 minutes, 2 times a week; 72 physical education lessons were conducted in each class during the study period. The test "Touch the ball" determined the ability to react quickly. The Student's T-criterion was used in statistical processing. After the end of the pedagogical experiment, the indicators of children in the control group improved by 3.1% (p>0.05); the positive dynamics can be explained by a natural increase in coordination abilities at the age of 8-9 years and the effectiveness of using the standard physical education program in Russian schools. The indicators of children in the experimental group improved by 9.3% (p<0.05). Such results can be explained by the effectiveness of using exercise standard classics in physical education lessons at school. The indicators of reacting quickly will significantly improve if children aged 8-9 also perform standard exercise classics during physical education lessons at school.